Financial and social reporting of Islamic banks in Malaysia : the discourse of corporate governance - Asri Marsidi (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2016)
Decent corporate governance practices are important and fundamental in today's corporate world, particularly in the growing and high future prospect of Islamic banking industry. In this respect, its linkages with disclosure at Islamic banks need to be well understood and developed for better sustainability of the industry. This study is hence conducted to examine the impact of corporate governance on the Islamic financial and social reporting (IFSR) of Islamic banks in Malaysia. Drawing on surveys and annual reports, this thesis seeks the views of accountants working in Islamic banks regarding the importance of items in the developed IFSR index. The annual reports are used to examine the score of the IFSR for the Islamic banks as well as to collect the data for the related variables. Multivariate regression is used as the main statistical technique to analyse the data. The findings suggest the importance of the financial part of the IFSR index followed by the importance of auditing and governance items, whereas the social items are viewed as fairly important. The findings on the social items may reflect that accountants are already aware of the need for social reporting components in Islamic banks although it yet to be considered as important as the financial items. The overall weighted score of IFSR have shown an increasing trend from 2007 to 2010. The scores, however, are still considered fair. As for the individual items, the score for finance items is classified as very good while the scores for social and governance items are categorised very poor and good respectively. The main findings suggest that board size is significant to explain the IFSR in Islamic banks in Malaysia. The other results indicate that board independence, board size, audit committee expertise, audit committee size, audit committee independence, and additional service of audit committee members significantly explain the IFSR for finance. Meanwhile, for the social items, the findings show that board size is significant in explaining the IFSR. As for the governance section of the IFSR, the results advocate that board independence and audit committee independence are significant to elucidate the IFSR. Theoretically, the thesis contributes to the body of literature through the use of Islamic agency theory. Further, the combination of quantitative, qualitative, mandatory, and voluntary requirements in the index is seen as capable of improving the disclosure of Islamic banks. The weighted index of IFSR on the other hand contributes towards enhancing the applicability of the disclosure. Moreover, the use of multivariate regression analysis contributes towards enriching the evidence on governance practices in Islamic banks. The findings may be useful to relevant stakeholders including the Islamic banks to review their disclosure level of IFSR to better discharge their accountability. At the same time, the findings contribute towards achieving a healthier formation of corporate governance mechanisms for better accountability and sustainability of Islamic banks in both Malaysia and abroad.